Alterations of Spontaneous Brain Activity in Hemodialysis Patients - Chen, Hui Juan; Qiu, Jie; Fu, Qingqing; Chen, Feng (Frontiers in Human Neuroscience, 2020)
Cognitive impairment is prevalent in hemodialysis end stage renal disease (ESRD) patients. It might be associated with poor prognosis. Nevertheless, the underlying mechanisms have not been completely clarified. This study explored spontaneous brain activity in ESRD patients on hemodialysis by using the amplitude of low-frequency fluctuation (ALFF). Nineteen ESRD patients on regular hemodialysis were included in this study. Eighteen age-, sex- and education level-matched volunteers were enrolled as the healthy control group. All participants had resting-state functional MRI scanning, neuropsychological tests and laboratory testing. ALFF was used for assessing intrinsic brain activity. Independent samples t-test was used for obtaining group difference. Spearman correlation analysis was applied to assess the association between ALFF changes, neuropsychological and clinical indices. Compared to the healthy control group, hemodialysis patients showed decreased ALFF in the precuneus, right angular gyrus/inferior lobule as well as increased ALFF in the left parahippocampus/hippocampus and right precentral/postcentral gyrus. The ALFF abnormalities in these regions were closely associated with hemoglobin levels. In addition, increased ALFF in the left parahippocampus/hippocampus showed negative correlation with the score of long delayed free recall. Hemodialysis patients had aberrant ALFF in the default mode network regions, particularly in the precuneus and parahippocampus/hippocampus, which may be correlated with neuropathological mechanisms involved in hemodialysis.